Self-Responsive Electrospun Nanofibers Wound Dressings: The Future of Wound Care - Biruk Fentahun Adamu; Jing Gao; Esubalew Kasaw Gebeyehu; Kura Alemayehu Beyene; Melkie Getnet Tadesse; Erkihun Zelalem Liyew (Advances in Materials Science and Engineering)
Skin wound management is a very difficult undertaking in the medical field. There is no information available concerning the wound beneath the bandages. Electrospun nanofibrous wound dressings stand out for their resemblance to extracellular matrix (ECM), increased surface-to-volume ratio, porousness, and capacity to encapsulate or load medications, among other distinctive qualities. Traditional antibacterial loaded electrospun nanofibrous wound dressings do not indicate the state of the wound and constantly release antibacterial chemicals even when there are no bacteria in the wound area. As a result, dressings that can track the condition of the wound and dispense medications as needed are crucial. Self-responsive wound dressings can release medications based on bacterial, oxygen spectra, pH, or infection responsiveness, reducing the need for antibacterial agents. Self-responsive mats, which are wound dressings that can release medications based on response to bacteria, oxygen species, and pH or infections, are required to reduce the overuse of antibacterial agents. Self-responsive electrospun nanofibrous mats can be used to monitor the condition of a wound by altering its color in response to an infection or a change in the pH of the wound. Electrospun nanofibrous wound dressings that are stimulus-responsive (self-responsive) are discussed in this review paper. Self-responsive electrospun nanofibrous wound dressings that are triggered by pH, temperature, light, bacteria, and oxygen species are discussed in detail after self-responsive smart materials or polymers used for electrospun nanofibrous wound dressings are covered in the first section of the review.